2016
DOI: 10.1080/09638288.2016.1243160
|View full text |Cite
|
Sign up to set email alerts
|

ImPACT: a multifaceted implementation for conversation partner training in aphasia in Dutch rehabilitation settings

Abstract: ImPACT: a multifaceted implementation for conversation partner training in aphasia inDutch rehabilitation settings. AbstractPurpose: Exploration of the clinical uptake of a novel conversation partner training (CPT) programme in aphasia in ten Dutch rehabilitation facilities and identification of its perceived facilitators and barriers in service providers, and the evaluation of the implementation methods used. Method:Ten rehabilitation centres took part in a multifaceted implementation of conversation partner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 48 publications
(71 reference statements)
0
21
0
Order By: Relevance
“…The final implementation study in aphasia was a qualitative before and after study conducted in the Netherlands (Wielaert et al . ). This study focused on implementing a conversation partner training programme in 10 rehabilitation centres.…”
Section: Introductionmentioning
confidence: 97%
“…The final implementation study in aphasia was a qualitative before and after study conducted in the Netherlands (Wielaert et al . ). This study focused on implementing a conversation partner training programme in 10 rehabilitation centres.…”
Section: Introductionmentioning
confidence: 97%
“…to an innovation such as CPT is exemplified in the 'fuzzy boundaries' of implementation discussed by Wielaert et al (2018), where an organisation with its interconnected activity systems adapts to the innovation, while the innovation is adapted to the local context, touching on "existing attitudes and expectations about aphasia treatment in service providers as well as service users" (Wielaert et al, 2018: 84).…”
Section: Collaborative and Transformative Learningexploring Alternatimentioning
confidence: 99%
“…Implementation science (e.g. Bauer et al, 2015), which was the basis for the PACT implementation study (Wielaert et al, 2018) may provide a more appropriate model for future investigations. In addition, we would argue that the radical exploration of experiences, 'learning what is not yet there' through incremental exploration and ongoing co-configuration work is highly relevant to other contexts such as student healthcare professional training, community work with families, friends and public service providers.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…One example is the Theoretical Domains Framework (TDF), which conceptualizes theories into 14 domains (Cane et al 2012), and is a useful tool in designing implementation interventions in clinical settings (Phillips et al 2015). Shrubsole et al (2019) recently reviewed the aphasia implementation literature and identified six implementation studies, with four involving CPT (Horton et al 2016a, Jensen et al 2015, Simmons-Mackie et al 2007, Wielaert et al 2018. The review authors found that none of the CPT studies included baseline measures, making it difficult to establish whether practice change had occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Despite increasing attention on improving CPT implementation, a number of ongoing implementation barriers have been identified. These barriers relate to organizational and resource constraints (such as a lack of time and staffing) (Horton et al 2016a, Simmons-Mackie et al 2007, Wielaert et al 2018, Jensen et al 2015, poor implementation leadership (Wielaert et al 2018), a lack of positive reinforcement and feelings of discomfort linked to unsuccessful interactions (Simmons-Mackie et al 2007, Jensen et al 2015, patient factors such as the severity of a person's aphasia (Horton et al 2016a, Jensen et al 2015 and a lack of opportunity to interact with PWA (Wielaert et al 2018). These ongoing implementation barriers indicate that it is likely necessary to review and modify implementation strategies as new barriers emerge or the organizational context changes.…”
Section: Introductionmentioning
confidence: 99%